A Case of Graves’ Disease Following Vaccination with the Oxford-AstraZeneca SARS-CoV-2 Vaccine: Case Report and Review of the Literature - Dalia Cuenca; Mercedes Aguilar-Soto; Moises Mercado (European Journal of Case Reports in Internal Medicine, 2022)
A 57-year-old man presented to the outpatient clinic with tremor, palpitations, weight loss and fatigue 1 week after receiving the first dose of the Oxford-AstraZeneca SARS-CoV-2 vaccine (ChAdOx1 nCoV-19). Laboratory studies showed a suppressed TSH with elevated total and free T4. Thyroid peroxidase and thyroglobulin antibodies were elevated but thyrotropin receptor autoantibodies were indeterminate. Thyroid scintigraphy with technetium Tc-99m pertechnetate revealed increased diffuse, symmetric uptake. The patient was treated with thiamazole 15 mg three times a day and propranolol with resolution of his symptoms and normalization of his thyroid function tests until discontinuation of the antithyroid drug 6 months after symptom onset.